2017
DOI: 10.1073/pnas.1706640114
|View full text |Cite
|
Sign up to set email alerts
|

Stalled replication forks generate a distinct mutational signature in yeast

Abstract: Proliferating cells acquire genome alterations during the act of DNA replication. This leads to mutation accumulation and somatic cell mosaicism in multicellular organisms, and is also implicated as an underlying cause of aging and tumorigenesis. The molecular mechanisms of DNA replication-associated genome rearrangements are poorly understood, largely due to methodological difficulties in analyzing specific replication forks in vivo. To provide an insight into this process, we analyzed the mutagenic consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 44 publications
10
31
0
Order By: Relevance
“…additionally, this high rate of fork collapse is partly suppressed when EXO1 is deleted, consistent with the previously observed stabilization of stalled replication forks in the absence of ExoI (53)(54)(55)(56). We therefore suggest that the essential function of the t-RPA complex is to promote replication of duplex telomeric DNA, rather than to protect termini from resection.…”
Section: Discussionsupporting
confidence: 90%
“…additionally, this high rate of fork collapse is partly suppressed when EXO1 is deleted, consistent with the previously observed stabilization of stalled replication forks in the absence of ExoI (53)(54)(55)(56). We therefore suggest that the essential function of the t-RPA complex is to promote replication of duplex telomeric DNA, rather than to protect termini from resection.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the role of E. coli RecQ in prevention of reversed-fork HJs may be shared by the budding yeast RecQ homolog Sgs1. 2D-gel electrophoresis of DNAfrom sgs1-deficient cells showed an increase in X-DNA structures near an engineered replication-fork barrier, supporting a role for Sgs1 in reducing reversed forks [37].…”
Section: Recq Prevents Reversed Forks In An E Coli Cancer Modelmentioning
confidence: 81%
“…Previously, we reported that the his2 :: URA3 -14xTus/ Ter cassette could trigger distinct types of localized mutations in URA3 (which confer resistance to 5-fluoro-orotic acid; 5-FOA) and that the Tus/ Ter -induced URA3 mutation rate was elevated ∼7-fold when the SGS1 gene was deleted (15). We therefore compared URA3 mutation rates for the his2 (non-telomeric region) and TEL06R Tus/ Ter barriers in wild-type (WT) and sgs1 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…To verify that the TEL06R phenotypes were due to replication fork stalling at Tus/ Ter , we compared the effects of reversing the orientation of the 21x Ter module such that the Tus/ Ter barrier, which we demonstrated previously to act in a polar manner (15), was in the ‘permissive’ (non-arresting) configuration. In this scenario, there was no detectable increase in 5-FOA resistant colonies (Supplementary Figure S1A and B), confirming that the Tus-dependent URA3 mutagenesis is due to replication fork stalling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation